The predictive ability of selfies and internet addiction on social appearance anxiety among Jordanian private university students - Mabreah, Shooroq; Al-Saliti, Rawan Abdul Mahdi Neyef; Omar, Abu AL Rub, Mohammed (Journal of Education and e-Learning Research, 2025)
The present study investigates whether selfies and Internet addiction predict social appearance anxiety among students at private Jordanian universities, considering the impact of gender, specialization, and academic stage using a descriptive correlational approach. 1,500 male and female students from private universities in Jordan participated in this study, selected through a non-probability convenience sampling method. Three measures were employed to achieve the study's results: the Selfie Inventory (SI), the Internet Addiction Inventory (IAI), and the Self-Administered Addiction Inventory (SAAI). Students at Jordan's private universities reported a medium level of selfies and Internet addiction. In contrast, social appearance anxiety was low. The results also revealed that the predictive model of the variables influencing social appearance anxiety was statistically significant (α = 0.05), with a joint contribution of the independent variables accounting for 45.00%. Selfies contributed the most, with a relative effect, explaining 38.30% of the total variance. Internet addiction accounted for 6.70% of the total variance. When selfies increase by one standard unit, social anxiety rises by 0.840. Similarly, when Internet addiction increases by one standard unit, social anxiety rises by 0.713 of a standard unit.